2015
DOI: 10.1038/ng.3399
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA4 inactivation defines a group of undifferentiated thoracic malignancies transcriptionally related to BAF-deficient sarcomas

Abstract: While investigating cohorts of unclassified sarcomas by RNA sequencing, we identified 19 cases with inactivation of SMARCA4, which encodes an ATPase subunit of BAF chromatin-remodeling complexes. Clinically, the cases were all strikingly similar, presenting as compressive mediastino-pulmonary masses in 30- to 35-year-old adults with a median survival time of 7 months. To help define the nosological relationships of these tumors, we compared their transcriptomic profiles with those of SMARCA4-mutated small-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
426
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(446 citation statements)
references
References 52 publications
9
426
0
11
Order By: Relevance
“…In this study, we report data to support further the existence of a class of rhabdoid-like tumors that not only represent a mesenchymal stem cell-like group of cancers that have misregulated SWI/SNF function (characterized by SWI/SNF loss of function mutations) but that are also dependent on PRC2 activity. This specific tumor class also shares clinical and histopathological features and has been found to carry a BAF-deficient sarcoma gene signature that is represented by developmental and embryonic stem cell programs (37). It is important to note that loss of SWI/SNF components alone does not predict sensitivity to EZH2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we report data to support further the existence of a class of rhabdoid-like tumors that not only represent a mesenchymal stem cell-like group of cancers that have misregulated SWI/SNF function (characterized by SWI/SNF loss of function mutations) but that are also dependent on PRC2 activity. This specific tumor class also shares clinical and histopathological features and has been found to carry a BAF-deficient sarcoma gene signature that is represented by developmental and embryonic stem cell programs (37). It is important to note that loss of SWI/SNF components alone does not predict sensitivity to EZH2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…An area of high interest is therefore to test the contribution of the tumor microenvironment in ARID1A-mutated in vivo models upon tazemetostat treatment. The cancer cell-of-origin appears to be a critical codeterminant of dependence on EZH2 activity; transcriptome analysis performed on a select number of SWI/SNF altered primary tumors revealed that SMARCA4-or INI1-deficient rhabdoid-like tumors clustered together and away from SMARCA4-deficient lung tumors, a more epithelial and more differentiated type of tumor (37). In addition, data from our CRISPR pooled screen show that knocking out SMARCA4 in a SMARCA2 low-expressing cell line (and vice versa) does not sensitize the cells to tazemetostat treatment further supporting the importance of the cell of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a distinct subset of intrathoracic undifferentiated tumors, termed SMARCA4-deficient thoracic sarcomas (SMARCA4-DTSs), was described by Le Loarer et al [1]. These tumors are characterized by the inactivation of SMARCA4 , a gene encoding an ATPase subunit of the switch/sucrose non-fermenting (SWI/SNF) chromatin remodeling complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the SWI/SNF proteins, SMARCA4 loss has been recently identified as the main or sole alteration driving small cell carcinoma of the ovary, hypercalcemic type [10]. Other SMARCA4-driven neoplasms include a rare subset of highly aggressive thoracic malignancies [11] as well as a subset of non-small cell lung cancer (NSCLC) [12] and others. To our knowledge, SMARCA4 loss has not been demonstrated to date in sinonasal tract carcinoma.…”
Section: Introductionmentioning
confidence: 99%